Pengendalian Persediaan Welding Gas Arcal-21 Dengan Metode EOQ dan Min-Max Pada PT. Beton Perkasa Wijaksana - Sari, Santika; Saputro, Annisa Putriana (UNISTEK, 2022)
PT. Beton Perkasa Wijaksana has experienced a drastic drop in product sales, resulting in an overload of raw materials in warehouses. The reason is because PT. Beton Perkasa Wijaksana lost cooperation with several foreign companies that had previously become regular customers who purchased products from PT Beton Perkasa Wijaksana. Therefore, it is necessary to control the inventory of raw materials to optimize the inventory in the warehouse. The purpose of this study was to determine the best value of inventory control from the comparison of the two methods, namely the EOQ method and the Min-Max method at PT. Beton Perkasa Wijaksana, so that the inventory of raw materials in the warehouse can be used optimally. The results showed that the value of safety stock, minimum inventory, maximum inventory, and total inventory cost that had smaller values was the EOQ method by minimizing 8% of the Min-Max method. Thus, the better method chosen is Economic Order Quantity (EOQ) by minimizing the direct cost of storing inventory and the inverse cost of ordering supplies